Post-cooling survival, growth and deformity rates in zebrafish embryos (Danio rerio) - Faria Paes, Maria do Carmo [UNESP]; Okada Nakaghi, Laura Satiko [UNESP] (Cambridge Univ Press, 2018)
This study investigated and analysed survival, growth and macro-and microscopic damage during the development of zebrafish embryos up to the adult stage after undergoing cooling. The embryos at 50% epiboly stage were selected, submerged in cryoprotectant solution of methanol and sucrose, cooled gradually to 0 +/- 2 degrees C temperature, and divided into two groups with different storage times (6 and 18 h). Subsequently, the embryos were reheated, rehydrated and incubated normally. The experiment lasted 5 months and, from hatching onward, the larvae were examined, collected and processed at pre-established time intervals. The hatching rate was significantly higher for the larvae stored for 18 h compared with the 6-h group. However, embryos from this group gave rise to a larger number of malformations, and these were much more severe compared with those in the 6 h group, which led to a higher mortality in the long term. Regarding larval length, the animals of the 6 h group had higher mean total length compared with the 18 h group, but both treatments were inferior to the control. Numerous macro-andmicroscopic malformations were observed and, in both treatments, only the morphologically normal individuals were able to develop to the adult stage, with organ development similar to the control, except for the gonads that were still undifferentiated in treated animals.
Keywords: Fish embryos; Low temperature; Malformation; Microscopy; Morphology